Effect of SARS-CoV-2 infection on asthma patients - Li, Xin-yu; Wang, Jing-bing; An, Hong-bang; Wen, Ming-zhe; You, Jian-xiong; Yang, Xi-tao (Frontiers in Medicine, 2022)
Background:Coronavirus disease 2019 (COVID-19), the novel coronavirus pneumonia, was caused by SARS-CoV-2, and the prevention and control of such an international pandemic situation are still very serious. Asthma is a major chronic inflammatory airway disease with an increasing prevalence and incidence worldwide. However, the relationship between asthma and COVID-19 is still unclear. The objective of this study was to determine the molecular mechanisms and identify potential drugs for the treatment of COVID-19 and asthma through bioinformatics analysis. Methods: We implemented a transcriptomic analysis to detect the common pathways and molecular biomarkers in asthma and COVID-19 that will help us understand the link between SARS-CoV-2 and patients with asthma. Here, two RNA-seq data (GSE147507 and GSE74986) from the Gene Expression Omnibus were used to detect mutually differentially expressed genes (DEGs) in patients with asthma and COVID-19 to find the shared pathways and the potential drug candidates. Results: A total of 66 DEGs was identified as common DEGs. Protein-protein interaction (PPI) network was established using a variety of bioinformatics methods. From the PPI network, five hub genes were identified. We found that asthma has some shared links with the progression of COVID-19. Additionally, protein-drug interactions with common DEGs were also identified in the datasets. Conclusion: We searched for potential interactions between COVID-19.and asthma using bioin-formatics databases and might be informative in treating patients with COVID-19. Further studies in populations affected by both diseases are recommended to elucidate the molecular drivers of the association between these two diseases.